ANALISA DAMPAK KEPEMIMPINAN KARISMATIK TERHADAP KINERJA KARYAWAN DI PEMERINTAH DAERAH KABUPATEN SUKOHARJO - Hasman Budiadi (Jurnal Ilmiah SINUS, 2016)
The Research represent study concerning “Analysis Affect Charismatic Leadership to Performance Employees at Sukoharjo”.Method was performed within this research is done survey in Sukoharjo, by propagating of kuesioner to all 65 employees to asses superior and to partinent functionary to assess its subordinate employees performance..Data Analisis was down by using analisis statistic test one sample and analysis of multiple regresi. Result of which is obtained from this research is : Indicator Manajemen of attention, manajemen of meaning, manajemen of trust, manajemen of risk and manajemen of feeling of charismatic leadhership fufilled but have don’t influence signifikan (in) Sukoharjo. Indicator manajemen of x’self is not fufilled at Sukoharjo and have influence with is signifikan to employees performance at Sukoharjo, but its influence negativity. With this research is expacted can give input that Leader better more careful and take a care in taking and applying Leadership theori, tobe accomodated existing condition and situation.Keyword : leadhership, charismatic, performance